On Wordsworth's Prelude. - Lindenberger, Herbert, 1929-2018 (Princeton legacy library., 1963)
In a series of closely related essays, Professor Lindenberger analyzes the language, style, imagery, and organization of Wordsworth's "Prelude.'' In precise detail and with richly relevant use of critical and historical materials, he demonstrates the variety and complexity of "The Prelude" leading the reader into a deepened understanding of one of the major long poems in the English language. Originally published in 1963. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905